To Pollute or Not To Pollute? Exploring MARPOL Efficiency in the Adriatic Sea - Grdović Gnip, Ana; Velkavrh, Žiga (Transactions on Maritime Science, 2022)
This study explores the efficiency level of the current international regulatory framework (MARPOL) in preventing sea pollution during maritime transportation. We employ a game-theoretic approach that models the decisions of shipowners and countries, with respect to the treatment and disposal of waste, where shipowners' decisions are based on comprehensive estimations of all waste management costs for all categories of waste (i.e. all MARPOL Annexes) differentiated across six types of standard risk vessels, while countries' decisions are based on estimates of all societal costs of (im)proper ship waste management. We focus on the Adriatic Sea case study and evaluate the game separately for members and non-members of the Paris Memorandum of Understanding (Paris MoU). Our main results seem to indicate that shipowners are generally motivated to be environmentally friendly if sailing Paris MoU waters. Otherwise, shipowners are merely motivated to pollute, due to low inspection rates and expected fines.This study explores the efficiency level of the current international regulatory framework (MARPOL) in preventing sea pollution during maritime transportation. We employ a game-theoretic approach that models the decisions of shipowners and countries, with respect to the treatment and disposal of waste, where shipowners' decisions are based on comprehensive estimations of all waste management costs for all categories of waste (i.e. all MARPOL Annexes) differentiated across six types of standard risk vessels, while countries' decisions are based on estimates of all societal costs of (im)proper ship waste management. We focus on the Adriatic Sea case study and evaluate the game separately for members and non-members of the Paris Memorandum of Understanding (Paris MoU). Our main results seem to indicate that shipowners are generally motivated to be environmentally friendly if sailing Paris MoU waters. Otherwise, shipowners are merely motivated to pollute, due to low inspection rates and expected fines.